Extermination as heritage - Menard, André (Revista Chilena de Antropología, 2017)
Genocide is codified by the notion of historical debt and thus becomes cultural heritage, and more precisely the moral heritage of a creditor of debt. The ideological, eminently colonial position, of transforming all extermination into an epiphenomenon of inexorable extinction implies depoliticizing historical violence. In this way, the -always- singular fact of a violence is translated into the plane of a universal equivalence (the plane of the Reason with capital letter) by which Humanity (also with capital letter), like a storekeeper of History, can realize the balance of costs and benefits at the end of the day.